Dynamic Strain Ageing Behaviour of Modified 9Cr-1Mo Steel under Monotonic and Cyclic Loading - Srinivas, N. C. Santhi; Verma, Preeti; Singh, Vakil (Elsevier Ltd, 2017)
Dynamic strain ageing (DSA) behavior of modified 9Cr-1Mo steel under uniaxial tensile and constant strain cyclic loading is presented in this paper. Tensile tests are carried out at different strain rates from 10-3 to 10-5 s-1 in the temperature range from room temperature to 600 °C. DSA has been established in the temperature range between 250 and 400°C in terms of peak in tensile strength, minima in ductility, serrated plastic flow and negative strain rate sensitivity. In the region of DSA dislocation substructure revealed high density of dislocations and features like kinks and bowing of dislocations are observed. Low cycle fatigue behavior was studied at 300°C, over a wide range of strain amplitudes at different strain rates. An inverse effect of strain rate was observed on cyclic stress response and fatigue life at 300 °C due to DSA.
Keywords: Modified 9Cr-1Mo steel; Dynamic Strain Ageing; Serrated Flow; Low Cycle Fatigue